Comparative Morphometric Rhizophora ApiculataFlower and Fruit in Two Areas with Anthropogenic Activities in West Dumai Coastal, Dumai City, Riau Province - Fernando, Muhammad Zebi; Efriyeldi, Efriyeldi; Mulyadi, Aras (Jurnal Natur Indonesia, 2021)
Morphometrics is a field that deals with variations and changes in the form (size and shape) of an organism or object. Anthropogenic is a human activity not only limited to the use or utilization of coastal resources, but also can be restorative and protective, thus causing complex disruption. The purpose of this study was to determine the morphometric differences of the flowers and fruits of R.apiculata mangroves in two regions with different anthropogenic activities in the mangrove ecosystem of Dumai City. This research was carried out in September 2019. From the results of the study it was found that in areas polluted by anthropogenic activity the average morphometrics of fruit (length and width) and leaves (length, width and length of the stems) Rhizophora apiculata were lower than those in the area not polluted by anthropogenic activity. At station I the oil content ranged from 0,0975 to 0,1251 ppm classified as polluted and at station II ranged from 0,072 to 0,111 ppm classified as not polluted.